Pengaruh Online Customer Review dan Online Customer Rating terhadap Keputusan Pembelian Produk Fashion di Shopee - Nafingatunisak Nafingatunisak; Heni Hirawati (Sains: Jurnal Manajemen dan Bisnis, 2022)
The research was conducted with the aim of analyzing the level of influence of online customer review and online customer rating variables on purchasing decisions for fashion products at Shopee using a population of all students of the Faculty of Economics, Tidar University by taking a sample of 96 respondents with certain criteria. This research is a quantitative research that uses regression analysis with the help of SPSS to solve problems. The data used is primary data with data collection techniques distributing questionnaires to respondents. This study uses the analysis technique of the F test, t test, and determination test which then results in the online customer review and online customer rating variables having a positive and significant influence on purchasing decisions. The percentage level of influence of online customer reviews and online customer ratings on purchasing decisions is 35.2%, while the other 64.8% is influenced by other factors.